Tourism satellite accounts – an information basis for the analysis of tourism expenditure - Shopova, M. (Економічний вісник Донбасу, 2017)
In order to develop management decisions promoting sustainable tourism development, strengthening its competitiveness and increasing the efficiency of the activities it covers, there must be timely statistical information available ensuring data comparability, completeness and detailing. This paper presents the methodological foundations of tourism satellite accounts. The emphasis is placed on their significance as a source of reliable and comparable statistical information on the importance of tourism for the economy in terms of expenditure, employment and gross domestic product. The contents of the tables containing data on tourism by activity and products are discussed and the theoretical aspects are illustrated through the empirical study of tourism expenditure (resident and non-resident visitors) in Bulgaria. Statistical methods of analysis are used to study the changes in their size and structure for the period 2008-2014. Для розробки управлінських рішень, що сприяють сталому розвитку туризму, утвердженню його конкурентоспроможності та підвищенню ефективності видів діяльності, що входять в його охоплення, необхідна наявність своєчасно наданої статистичної інформації, яка гарантує сумісність, повноту і деталізацію даних. У публікації представлено методологічні основи сателітних рахунків туризму. Акцентується увага на їх значенні як джерела достовірної і порівнянної статистичної інформації про значимість туризму для економіки з точки зору витрат, зайнятості та валового внутрішнього продукту. Розглядається зміст таблиць, які надають дані про туризм за видами діяльності і продуктів. Теоретичні аспекти проілюстровані емпіричним дослідженням витрат на кінцеве споживання туристів (резидентів і нерезидентів) в Болгарії. За допомогою статистичних методів аналізу досліджено зміни їх розміру і структури за період 2008-2014 рр. Для разработки управленческих решений, способствующих устойчивому развитию туризма, утверждению его конкурентоспособности и повышению эффективности видов деятельности, входящих в его охват, необходимо наличие своевременно предоставляемой статистической информации, гарантирующей сопоставимость, полноту и детализацию данных. В публикации представлены методологические основы сателлитных счетов туризма. Акцентируется внимание на их значении в качестве источника достоверной и сравнимой статистической информации о значимости туризма для экономики с точки зрения расходов, занятости и валового внутреннего продукта. Рассматривается содержание таблиц, предоставляющих данные о туризме по видам деятельности и продуктам. Теоретические аспекты проиллюстрированы эмпирическим исследованием расходов на конечное потребление туристов (резидентов и нерезидентов) в Болгарии. Посредством статистических методов анализа исследованы изменения их размера и структуры за период 2008-2014 гг.